High genetic diversity and low differentiation in North American Margaritifera margaritifera (Bivalvia: Unionida: Margaritiferidae). (17th February 2018) - Zanatta, David T; Stoeckle, Bernhard C; Inoue, Kentaro; Paquet, Annie; Martel, André L; Kuehn, Ralph; Geist, Juergen
Abstract: Information on the genetic diversity and population genetic structure of threatened species is important for guiding management decisions. Margaritifera margaritifera (freshwater pearl mussel) occurs across western Russia, north and central Europe, and Atlantic drainages of north-eastern North America (NA). European populations of M. margaritifera are considered endangered, whereas NA populations are thought to be relatively secure. As such, the population genetics of M. margaritifera occurring in European rivers is relatively well studied while that of NA populations is not known. In this study, we investigated the genetic diversity and differentiation of M. margaritifera in Canada and the USA. Genetic diversity indices calculated from nine microsatellite loci were relatively high in the NA population. Analyses of genetic structure indicated that a single panmictic population exists for M. margaritifera in NA. However, there was evidence of substructure in some tributaries of the St. Lawrence River in Québec, Canada. The NA population of M. margaritifera has low genetic differentiation and high diversity, possibly resulting from large population size and high gene flow. Consequently, conservation of this species should focus primarily on maintaining favourable habitat conditions and connectivity for host fish.